Intracranial infections of Candida albicans and Mycobacterium intracellulare associated with CARD9 deficiency: case report and review of literature - Tang, Congchen; Chen, Chao; Lv, Xiaoju; Xie, Yi; Xiong, Li; Long, Jiangchao; Ye, Hui (Frontiers in Immunology, 2025)
BackgroundInvasive candidiasis, most commonly caused by Candida albicans, poses a significant mortality risk and is challenging to treat. Non-tuberculous mycobacterial infections are opportunistic and linked to immune impairment. Caspase recruitment domain-containing protein 9 (CARD9) represents a class of proteins that incorporates the caspase recruitment domain, and its deficiency follows a strict autosomal recessive inheritance pattern, resulting in an impaired immune response.Case presentationA 51-year-old male who was admitted to the hospital 3 years ago because of recurrent fever accompanied by headache. The causative factor remains elusive and symptomatic treatment yielded unsatisfactory results. Next-generation sequencing (NGS) of cerebrospinal fluid (CSF) identified the fungus as C. albicans. Following antifungal therapy, the patient experienced relief from fever and headache; however, he subsequently developed a hydrocephalus. CSF culture indicated NTM—Mycobacterium intracellulare, prompting the initiation of anti-NTM treatment. Given the recurrent infections, we collected peripheral blood for whole exome sequencing, which revealed a CARD9-deficient homozygote with a new mutation site identified as c.175C>T (p. Arg59Trp). The patient was hospitalized on 8 occasions for diagnostic assessment and treatment. Presently, antifungal treatment has been discontinued after 9 months of therapy, while anti-NTM therapy is being maintained, with the patient reporting no fever or other discomforts.ConclusionThe c.175C>T (p. Arg59Trp) mutation is a novel CARD9 gene mutation and is probably damaging. Clinicians should consider immune impairment as a contributing factor in the management of fungal infections among non-HIV/AIDS patients. For such patients, conducting multiple CSF and blood cultures and employing new technologies such as NGS are advisable. Treatment of NTM and C. albicans requires personalized treatment plans. Moreover, the long-term follow-up should not be overlooked.